THE ANALYSIS OF READINESS IMPLEMENTATION OF INTEGRATED REPORTING (IR) ON COMPANIES PUBLISHING SUSTAINABILITY REPORT IN 2015 - Dewanti, Patriani Wahyu; Anantha, Tegar Galang (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
This study aimed to analyze the companys readiness to implement the Integrated Reporting (IR). The objective of the implementation is to enable companies to re-evaluate their business activities in order to create value in a sustainable manner so that the company can present high quality information to stakeholders.                The population of this research are companies that had published Sustainability Report (SR) and listed on the Indonesian Stock Exchange (IDX) in 2015 which amounted to 39 companies. The data analyzed in this study are secondary data from the annual report (AR) and sustainability report (SR) of each company that was published in 2015. The analysis uses 61 indicators that reflect IR eight elements in the <IR> Framework. Research data analysis using descriptive statistical analysis in tabular form the companys readiness categorization.               The result showed that: 31% companies categorized as well prepared to implement the Integrated Reporting, Furthermore 23% companies classified as prepared to perform the Integrated Reporting, whereas 46% companies categorized as unprepared to implement the Integrated Reporting. Keywords: Sustainability Reporting, Integrated Reporting